Examining how scientists 'do' gender: An analysis of the representations of hegemonic masculinity and emphasized femininity on The Big Bang Theory. Issue 2 (1st September 2018) - Blosser, Emily
The television sitcom The Big Bang Theory (2007–present) portrays the lives of a group of highly intelligent but socially awkward scientists. The show consistently attracts an audience of approximately fifteen million viewers each week and thus offers a powerful opportunity to examine how scientists are represented in popular fiction. Drawing on sociological gender theories, this article examines episodes from the first seven seasons of the show to explore how it depicts scientists as individuals who fail to live up to standards of hegemonic masculinity and emphasized femininity. Implications of such imagery for public understandings of scientists and for issues of gender inequality are discussed.